2018 International Conference on Radar (RADAR) 2018
DOI: 10.1109/radar.2018.8557296
|View full text |Cite
|
Sign up to set email alerts
|

Using VHF Navigation Aid to Estimate Radar Cross Section of Airliners by Inverting the Radar Equation

Abstract: The VHF Omnidirectional Range (VOR) navigation aid system can be used as donor of signal for passive radar experiments. An experiment was set up close to a VOR beacon to detect airliners and to analyze their radar cross section in function of their attitude. This paper presents the configuration of the trials, the adapted signal processing and the detection results obtained for one of the detected targets. The radar cross section (RCS) was estimated from the computation of power budget in radar equation. An an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 1 publication
2
8
0
Order By: Relevance
“…3 shows the histograms of bistatic RCS of the airplanes models (small, medium and large) for HH (φ-φ) and HV (φ-θ) cases and for all scattered and incident angles considered lines above. We can see that most of the RCS values are concentrated between 0 dBsm and 40 dBsm (in accordance with [3], Airbus 321 is comparable to the model of medium size used lines above). Most importantly, in global, RCS values between the airplanes are very similar, making the discrimination difficult from RCS only.…”
Section: B Simulation Results -Rcssupporting
confidence: 86%
See 2 more Smart Citations
“…3 shows the histograms of bistatic RCS of the airplanes models (small, medium and large) for HH (φ-φ) and HV (φ-θ) cases and for all scattered and incident angles considered lines above. We can see that most of the RCS values are concentrated between 0 dBsm and 40 dBsm (in accordance with [3], Airbus 321 is comparable to the model of medium size used lines above). Most importantly, in global, RCS values between the airplanes are very similar, making the discrimination difficult from RCS only.…”
Section: B Simulation Results -Rcssupporting
confidence: 86%
“…V. CONCLUSIONS AND PERSPECTIVES It has been shown, through simulations, that, globally, the bistatic RCS of airplanes of different sizes (large, medium and small) are similar, which makes difficult their discrimination on the sole basis of RCS value. It has been also shown that it is more sensible to look for the angular frequency (extraction of this information can be done as in [3]) of the bistatic RCS when the airplane is moving in order to discriminate the planes by sizes (larger planes will scatter power with finer and more peaks). These simulation results, can be used to synthesize bistatic RCS evolution for arbitrary trajectories (for example based on real trajectories) and include many VORs and different positions of receiver, in order to consider multiple scenarios based on real data to train neural networks (which need a large collection of data that many times are not available by measurement) on the recognition of airplanes.…”
Section: B Examples Of Collected Datamentioning
confidence: 99%
See 1 more Smart Citation
“…As for the radar range equation, it can be applied to estimate the radar cross section (RCS), but the RCS is estimated in the far field [18]. The unique RCS characteristic is calculated to predict a target state based on the radar equation for 26 GHz and 79 GHz short range vehicular radars.…”
Section: Introductionmentioning
confidence: 99%
“…Although ground reflection interference [9] (which may also interfere with the noise at the receiver), wave polarization [8] and aeroplane heading [10] can make extremely difficult the extraction of these values in some particular cases. By exploiting the automatic dependent surveillance‐broadcast (ADS‐B) data broadcasted (L band) by the aeroplanes, their position and heading are then known and their BiStatic‐RCS (BS‐RCS), that is, RCS for separated transmitter and receiver, can be effectively estimated as in [5].…”
Section: Introductionmentioning
confidence: 99%